OPTIMALISASI METODE MURAJA’AH DALAM PEMBELAJARAN TAHFIZH DI SD IT MADANI 2 ISLAMIC SCHOOL PAYAKUMBUH - Finda Fadilla; Hamdi Abdul Karim; Yuliana (CV. ADIBA AISHA AMIRA, 2024)
The background of this research is to fulfill assignments in student activities at UIN SMDD Bukittinggi as well as to determine and optimize students’ ability to memorize the Qur’an at SD IT Madani 2 Payakumbuh using the muraja’ah method in tahfizh learning. The aim of this research is to find out what the students’ ability to read and memorize the Qur’an at SD IT Madani 2 Islamic School Payakumbuh is like, what kind of methods are applied to students in learning to read and memorize the Qur’an and to help students teachers to improve students’ ability to read and memorize the Koran. This research also aims to optimize the ability to read, memorize and write the Koran through the muraja’ah method at SD IT Madani 2 Islamic School Payakumbuh. This research was conducted at SD It Madani 2 Islamic School Payakumbuh with the title optimizing the ability to memorize the Qur’an through the muraja’ah method at SD It Madani 2 Islamic School Payakumbuh. The problem examined in this research is what is the level of memorization of the Qur’an that students have at SD IT Madani 2 Islamic School Payakumbuh, what is the method of memorizing the Qur’an applied by teachers to students in tahfizh learning, what are the difficulties? Students face in memorizing the Qur’an. The method used in this research is a qualitative research method which aims to analyze how to improve students’ ability to memorize the Koran through implementing the muraja’ah method in tahfizh learning. The data collected in this research was through observation, interviews and direct practice in tahfizh learning at SD IT Madani 2 Islamic School Payakumbuh. The results obtained in this research are: First, the ability to memorize the Koran of students at SD IT Madani 2 Islamic School Payakumbuh has reached the memorization target limit set by the Tahfizh teacher. Second, the ability to memorize the Al-Qur’an of students who are still not fluent in memorizing the Al-Qur’an can be improved through the implementation of the muraja’ah method which is held at SD IT Madani 2 Islamic School Payakumbuh.